Morphological and Physiological Response of Maize (Zea mays L.) to Drought Stress during Reproductive Stage - Saba Yasin; Francisco Zavala-García; Guillermo Niño-Medina; Pablo Alan Rodríguez-Salinas; Adriana Gutiérrez-Diez; Sugey Ramona Sinagawa-García; Eleazar Lugo-Cruz (Agronomy, 2024)
Maize is among the most significant crops in the world regarding production and yield, but it is highly sensitive to drought, which reduces the growth, photosynthetic efficiency, grain quality, and yield production of a plant. Quantum yield efficiency of photosystem II is a critical photosynthetic component that is susceptible to drought stress. This study intended to investigate the effects of drought stress on growth and morpho-physiological parameters using three maize hybrids (‘P-3011w’, ‘P-3092’ and ‘iku20’) with contrasting soil moisture contents (100%, 40%) at the pre-flowering stage. The stress treatment (40%) was initiated at stage V7, for a period of 15 days; the experimental units were established in a completely randomized design with split-plot arrangement along with three repetitions in 42 L pots using a substrate of peat moss, black soil and poultry manure (1:2:1). The morphological, growth-related and physiological parameters were assessed, including chlorophyll fluorescence (Fv/Fm), which was measured using a LiCor-6400-40 fluorometer. The results showed that all morphological, growth-related and physiological variables decreased under drought stress during the reproductive stage, with the exception of leaf temperature and intercellular CO2 concentration, which increased by 12% and 54%, respectively. Drought stress significantly reduced the photosynthetic chlorophyll fluorescence (43%), due to damage to photosystem II. The lowest percentage of damage to photosystem II (34%) was observed in the iku20 genotype. In contrast, P-3011w and P-3092 had the highest levels of significantly similar damage (49% and 46%, respectively). The correlation analysis showed a highly positive interaction of chlorophyll fluorescence (Fv/Fm) with net photosynthetic rate and stomatal conductance under drought conditions, and multiple regression analysis revealed that the maximum effect on net photosynthetic rate under drought was due to the damage it caused to photosystem II. Thus, iku20 might have a tendency to be able to withstand drought stress in the dry northeast region of Mexico. Overall, we concluded that the photosystem II was negatively impacted by drought stress thus causing a reduction in all physiological, morphological and growth-related variables.